Design and development of real time monitoring and control system for water quality in recirculating aquaculture system - Azizi Ali (Institut Oseanografi, 2012)
This thesis presents the implementation of process control system technique into the monitoring and control for the recirculating aquaculture system (RAS). This study focuses on the development of the real time monitoring and control system for water quality in RAS. The design and development process consists of four stages. The first stage is the design and development of the pilot scale RAS. The second stage is the development of the data acquisition module.